Revised Ordinances and Charter of the City of Laramie, Wyo., with Constitutional Provisions and Legislative Enactments Governing the Same, at 89, ch. 5, § 3 (1900) - (:unkn) unknown (General Publisher, 1900)
Hereafter it shall be unlawful for any person in the City of Laramie to keep, carry or bear upon the person any sling, catapult, spring or air gun, or nigger shooter, used for the hurling of missiles or stones, and every person violating the provisions of this section shall, upon conviction, be fined in a sum not exceeding five dollars.
--
Keywords: POSSESSION